The Vanishing Country - Hurtig, Mel. (Toronto McClelland and Steward Inc., 2002)
This book is about the tragic sellout of Canada. It`s about a selfish, greedy, and powerful plutocracy abandoning the work of generations of Canadians, and the dreams of the vast majority of the people who live in this country, for American standarts, values, and priorities.
Keywords: Country Studies